You saw) in the Noble Qur’an between the grammatical connotation and the Qur’anic context - Hussein, Basem Mohammed (Al-Adab Journal, 2015)
The research is a quick journey with the Quranic construct ’ara’aita’ (have you seen? / can you see). There is an attempt to analyze and study parts of this construct in the light of its grammatical sense. It has been shown that when the construct is prefixed with the letter ’kaf’ (k), then it gives the sense of emphasis, specialty and exaggeration such that to urge the addressee to think and share the speaker thinking. The researcher found out that for this verb to be transitive depends on its original sense which is ’have you seen, do you know, tell me’. The researcher concluded that the Quranic context of this construct is highly related to its grammatical meaning which shows up according to the degree of its constructs’ variation. This opens the door wide for the researchers to investigate its uses within Quranic context which is, in turn, often relevant to a great issue that gives the sense of wonder and exclamation